Present state and perspectives for the southern Brazil shelf demersal fisheries - Haimovici, Manuel (2012)
Submitted by Michele Fernanda (michele_fernandas@hotmail.com) on 2012-07-24T03:38:16Z No. of bitstreams: 1 Present state and perspectives for the southern Brazil shelf demersal fisheries.pdf: 430435 bytes, checksum: 875a703ba9a35ebdc6c97d358cfa5672 (MD5)